Physicochemical Properties of Palm Kernel Oil and Palm Kernel Olein Blends - Abd Rashid, Norizzah; Nurhanis Jumari, Fatin; Omar, Zaliha (International Journal of Engineering and Technology, 2019)
Palm kernel oil (PKO) and palm kernel olein (PKOo) have limited application due to rapid crystallisation properties and excessive foaming during heating, respectively. In this study, a series of PKO and PKOo blends were prepared at different concentration and analysed for slip melting point (SMP), solid fat content (SFC), triacylglycerols (TAGs) composition, thermal and morphological properties. The addition of 90% RBDPKOo caused the SMP to decrease from 27.8Â°C to 23.80Â°C. All the samples show steep SFC melting profile from 0Â°C to 30Â°C. The onset crystallisation temperature of RBDPKO was delayed with the addition of 90% PKOo from 9.73Â°C to 5.80Â°C and totally melted at lower melting temperatures.Â It was observed that the addition of RBDPKOo caused the crystals to be spherulitic, scattered and less aggregated with each other. The addition of RBDPKOo reduced the compositions of the main TAG of RBDPKO such as LaLaLa, LaLaM and CLaLa. Therefore, through blending the physicochemical properties of the RBDPKO and RBDPKOo could be changed. Hence, their applications in food could be widened.Â Â